PERAN GURU DALAM MENDUKUNG PERKEMBANGAN BAHASA ANAK SPEECH DELAY (STUDI KASUS KUALITATIF PADA ANAK KELAS B USIA 6-7 TAHUN DI TKIT AL-MUHAJIRIN CILEGON-BANTEN) - Aulia Astagina; Dina Kusuma Wardhani; Fahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the role of teachers in supporting children's language development (speech delay). The purpose of this study is to identify the role of teachers, the factors causing speech delay in early childhood, and to understand the development of children's language abilities after receiving guidance and stimulation from teachers. This study uses a qualitative approach with a case study method, employing data collection techniques such as observation, interviews, documentation, and field notes. The research subjects in this study are one early childhood child aged 6-7 years at TKIT Al-Muhajirin, Cilegon City, who experiences speech delay. Data analysis uses the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The findings of the study indicate that the role of teachers carried out consistently and supported by a responsive environment can help optimize the language development of children experiencing speech delay. Keywords: The role of teachers, language development, early childhood, speech delay.